Visitor Willingness to Pay U.S. Forest Service Recreation Fees in New West Rural Mountain Economies. (February 2014) - Keske, Catherine M. H.; Mayer, Adam
This study uses a contingent valuation model to evaluate visitors' stated willingness to pay (WTP) for recreation at Colorado "Fourteeners": peaks that rise higher than 14, 000 feet. The study also assesses the respondents' self-reported response uncertainty. One scenario queries respondents about a hypothetical situation in which they would pay an entrance fee where 80% of the funds are used on-site, and the degree of certainty with which they answered the question. Like prior articles from this 6-year project (2006-2012), results indicate a high WTP for recreation on Colorado Fourteeners. Results reveal that 62% of respondents are willing to incur an additional fee of $20 or less to recreate at the study site. Regardless of whether or not the respondent is willing to pay an additional fee for recreation, approximately 90% of respondents report a high level of certainty in their stated answers to both the WTP and the fee questions, which could be connected to the recreators' sense of place on Fourteeners. Therefore, recreators exhibit clear preferences and low uncertainty in their WTP for general cost increases and localized access fees. Implications could have a complex effect on when, if, and how fees should be applied in "New West" economies reliant on revenues from recreation.